Nail Disorders as Manifestations of Systemic Diseases - Ramdhini, Tisya Nasywa; Setiasari, Febi Jian; Salsabila, Adilah Nur; Pramudiantara, Gede Naradhea; Nabila S., Aqilla Nasywa; Ilham, Muhammad Fadani; Josafat, Anom (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Nails are often overlooked in clinical examinations, despite their ability to provide important information regarding systemic health conditions. Changes in nail morphology, color, and growth frequently reflect underlying metabolic, hematological, autoimmune, infectious, and neoplastic disorders. This article aims to comprehensively review various nail abnormalities as manifestations of systemic diseases. The method used was a narrative literature review with article searches conducted through PubMed and Google Scholar databases using the keywords nail abnormalities, systemic diseases, nail manifestations, and clinical signs. Articles published between 2015 and 2025 were selected based on relevance, with inclusion criteria consisting of clinical studies, case reports, and reviews discussing the association between nail abnormalities and systemic diseases, while excluding literature that focused solely on local nail disorders without systemic relevance. The results indicate a range of nail abnormalities associated with systemic diseases, including splinter hemorrhage in infective endocarditis and vasculitis, clubbing finger in lung cancer and cyanotic congenital heart disease, subungual hyperkeratosis in psoriasis and onychomycosis, nail bed pallor in chronic anemia, koilonychia in iron deficiency anemia, onychomycosis in diabetes and immunodeficiency, as well as yellow nail syndrome related to lymphatic dysfunction, respiratory disorders, and autoimmune diseases. Other manifestations such as leukonychia, Mees’ lines, Terry’s nails, half-and-half nails, and Beau’s lines were also identified in metabolic disorders, renal disease, and toxin exposure. In conclusion, nail examination can serve as a valuable non-invasive method in detecting systemic diseases. Early identification of nail changes has the potential to assist clinicians in establishing diagnoses, accelerating interventions, and improving the quality of patient management.